Medication compliance in Kawasaki disease patients with coronary involvement - Okawa, Surnio; Sonobe, Tomoyoshi; Aso, Seijiro; Tsuchiya, Keiji; Imada, Yoshio; Kataoka, Tadashi (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1995)
Kawasaki disease with coronary involvement requires long term antithrombotic therapy but because it is an asymptomatic condition. Consistency in taking medication is a problem. We have experienced a case of myocardial infarction occurring due to non-compliance in medication use. As a result a survey was conducted on medication compliance in our 94 outpatients to study non-compliance. The survey was performed by examining outpatient clinical charts and counting the actual days covered by prescriptions in a year. The survey revealed that 64% of the patients were regular in their hospital visits to pickup prescriptions as scheduled, 14% were covered by prescriptions for 300 days or more but less than 1 year, and 22% were covered less than 300 days. Non-compliance predominated in older children and mildly involved coronary cases. To improve medication compliance, we have to recognize that medication non-compliance is not infrequent among patients of Kawasaki disease with coronary involvement. More precise disease education for both parents and patients, especially for young children, appears to be necessary.